Critical Analysis of Snuhi - Euphorbia Neriifolia (Upavisha- Poisonous Plant) and its Application as a Therapeutic Aid - Sorab Gaind, (AYUSHDHARA, 2021)
Traditional system of medicines has vast applications of poisonous plants; hence the knowledge about poisonous plant and its therapeutic effects becomes very essential to develop a new drug for the new diseases like Covid 19 and other diseases. Many research studies have showed that the poisonous medicinal plants are endowed with properties like Antidiabetic, Anticancer, Antibacterial, Antifungal, and Cytogenetic effect. This study focused on one such drug called Snuhi - Euphorbia Neriifolia, a Upavisha or a poisonous plant to evaluate its therapeutic effects, which would be helpful for the mankind after the proper Shodhana (purification), by conducting experimental studies, toxicity studies and thereby applied in various diseases for its therapeutic benefits and to relieve the sufferings of the patients.